The Stereoacuity-Dependent Concordance between Preferred Fixating Eye and Sighting Dominant Eye in Paediatric Intermittent Exotropia. (2nd September 2019) - Zhou, Lu; Zhou, Qing; Bi, Hua; Chen, Yanxu; Chen, Zhijun; Wu, Haoran; Huang, Zhenping; Zhang, Bin
ABSTRACT: Objective : To investigate if the concordance between sighting dominance and fixation preference depends on stereoacuity in children with intermittent exotropia (IXT). Methods : A total of 160 children (aged 7.24 ± 2.14 years, range 4–13 years) with the basic type of IXT at distance participated in the study. Binocular fusion and vergence were evaluated with synoptophore. Stereoacuity was assessed using the Titmus stereo test. The hole-in-the-card test was used to determine sighting dominance, while the eye of fixation preference was determined by the cover-uncover test. The chi-squared test was used to evaluate whether a distribution was different from the chance distribution. The Kappa value was computed to quantify the concordance between fixation preference and sighting dominance. Results : The mean deviations were 19 ± 4.58 prism diopters (PD) and 18.9 ± 4.47 PD for at distance and near, respectively. The mean amplitude of divergence was 5.34 ± 1.89 PD, and the mean amplitude of convergence was 14.08 ± 4.96 PD. Subjects were categorized as having either good (40–60 seconds of arc, n = 41), moderate (80–140 seconds of arc, n = 46), poor (≥ 200 seconds of arc, n = 45), or having no measurable stereoacuity (n = 28). The concordance between sighting dominance and fixation preference was high in subjects with good (Kappa = 0.858) or moderate (kappa = 0.812) stereoacuity, but it decreased quickly in subjects with poor stereoacuity (kappa = 0.496) or no stereopsis (kappa = 0.563). Conclusions : In pediatric patients with IXT, the concordance between sighting dominance and fixation preference depends on stereoacuity. The results from these two tests become increasingly incongruent as stereoacuity deteriorated.